2019
DOI: 10.1007/s10854-019-00938-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of post-process annealing on optical and electrical properties of mixed HfO2–TiO2 thin film coatings

Abstract: In this paper a comparison of electrical and optical properties of mixed hafnium-titanium oxides is described. Thin films were deposited with the use of the magnetron co-sputtering method. For further analysis (Hf 0.52 Ti 0.48)Ox and (Hf 0.29 Ti 0.71) Ox coatings, which were amorphous directly after the deposition process, were chosen,. Moreover, post-process annealing was also performed in order to compare the electrical and optical properties of amorphous and nanocrystalline thin films with the same material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…This was an expected result as the monoclinic HfO 2 films (Figure d) were obtained and characterized in our experiments too. The permittivity values of as-grown Hf x Ti 1– x O y films that contained the orthorhombic phase were comparable to those of the films crystallized during the postgrowth annealing. , For instance, values of 51–55 at x = 0.30 and 30–37 at x = 0.66 were measured for our films, while the relative permittivity values, obtained in earlier studies after the postgrowth annealing of amorphous films at 500–650 °C, were 51 at x = 0.29, 51 at x = 0.30, and 40 at x = 0.64 . Corresponding values of amorphous films were 25 at x = 0.29, 31 at x = 0.30, and 25 at x = 0.64 …”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…This was an expected result as the monoclinic HfO 2 films (Figure d) were obtained and characterized in our experiments too. The permittivity values of as-grown Hf x Ti 1– x O y films that contained the orthorhombic phase were comparable to those of the films crystallized during the postgrowth annealing. , For instance, values of 51–55 at x = 0.30 and 30–37 at x = 0.66 were measured for our films, while the relative permittivity values, obtained in earlier studies after the postgrowth annealing of amorphous films at 500–650 °C, were 51 at x = 0.29, 51 at x = 0.30, and 40 at x = 0.64 . Corresponding values of amorphous films were 25 at x = 0.29, 31 at x = 0.30, and 25 at x = 0.64 …”
Section: Resultssupporting
confidence: 78%
“…9,17 For instance, values of 51−55 at x = 0.30 and 30−37 at x = 0.66 were measured for our films, while the relative permittivity values, obtained in earlier studies after the postgrowth annealing of amorphous films at 500−650 °C, were 51 at x = 0.29, 17 51 at x = 0.30, 9 and 40 at x = 0.64. 9 Corresponding values of amorphous films were 25 at x = 0.29, 17 31 at x = 0.30, 9 and 25 at x = 0.64. 9 These results demonstrate that the application of seed layers leading to the in situ crystallization during the deposition allowed a considerable reduction of processing temperatures needed for producing dielectrics with high permittivity.…”
Section: Growth Rate and Compositionmentioning
confidence: 46%
See 2 more Smart Citations
“…By comparing with the standard card PDF#73-0445 of La 2 Hf 2 O 7 , it was found that the corresponding peak appeared at 600 • C. The XRD analysis shows that with the increase in temperature, the diffraction peak position of the sample obviously moves to a small angle, revealing the existence of tensile stress inside the sample. The crystallite size was calculated using the Debye-Scherrer formula [32][33][34]:…”
Section: Structure Analysismentioning
confidence: 99%